Factors Influencing Farmers Participation in the Vaccination Program against Anthrax in Bogor District, Indonesia - Chaerul Basri; Etih Sudarnika; S Dwidzuriputra (Acta VETERINARIA Indonesiana, 2019)
Bogor District is one of the endemic areas of anthrax cases in Indonesia. The mass vaccination campaign on livestock including goats and sheep needs to be done to prevent the spread of the disease. The willingness of farmers to participate is the main key to the success of this vaccination campaign. This study aimed to identify the factors that influence the willingness of goat and sheep farmers to participate in vaccination programs against anthrax in their farms. A total of 60 goat and sheep farmers were randomly selected from 3 villages located in the region with the highest incidence of cases in Babakan Madang Subdistrict. Data was collected through direct interviews using a structured questionnaire. Analysis to determine risk factors was carried out by chi square test and continued by calculating the value of relative risk (RR) to measure the magnitude of the influence of these factors. The results showed that the factors that influenced the farmers to be willing to participate in the anthrax vaccination program were history that had been directly counseled with RR values 2,844 (95% CI = 1,547-5,288) and history of having constrained to vaccinate their livestock with RR values 1,960 (95% CI = 1,203 - 3,193). Based on these findings it is recommended to increase farmer participation in mass vaccination programs against anthrax can be done through increasing communication, information and education activities and minimizing constraints for farmers to vaccinate their livestock.